Renal haemodynamic characteristics in patients with lupus nephritis. Issue 4 (1st April 1998) - Nakano, Masaaki; Ueno, Mitsuhiro; Hasegawa, Hisashi; Watanabe, Takeshi; Kuroda, Takeshi; Ito, Satoshi; Arakawa, Masaaki
Abstract : OBJECTIVE: To clarify the characteristics of renal haemodynamics in patients with lupus nephritis (LN). METHODS: The glomerular filtration rate (GFR) and renal plasma flow (RPF) of 37 patients with active LN were studied longitudinally over an interval of 8 to 144 weeks during treatment with corticosteroids or cytotoxic drugs, or both. All patients had clinical renal disorders and underwent renal biopsies. RESULTS: Analysis of renal biopsy specimens showed that 31 patients had class IV LN. Class II, III, and V LN were present in two patients each. The average GFR increased significantly from 65.4 (SD 33.0) in the pretreatment stage to 86.6 (31.6) ml/min in the post-treatment stage, accompanied by an improvement in urinary or immunological abnormalities, or both. On the other hand, RPF decreased significantly from 625.2 (243.0) to 519.8 (179.0) ml/min. Therefore, the filtration fraction (FF) increased significantly from 10.7 (4.3)% to 16.8 (3.7)%. Low FF was recognised predominantly in patients with class IV LN, but was also observed in patients with other classes. The FF returned towards normal irrespective of the degree of GFR recovery. No significant changes were observed in the levels of blood pressure. CONCLUSION: A reduction in GFR out of proportion to the reduction in RPF as demonstrated by the low FF values was related to the severity of LN or disease activity, or both. Therefore, relative evaluation of GFR and RPF, namely the determination of FF, may be a useful clinical parameter to determine the status of LN.